Spatial remapping of the visual world across saccades. - Bays, P; Husain, M (2007)
Recent research has identified neurons in the visual system that remap their receptive fields before a saccade. The activity of these neurons may signal a prediction of postsaccadic visual input, derived from an efference copy of saccadic motor output. Such a prediction is often thought to underlie our perception of a stable visual world, by compensating for the shifts in retinal image that accompany each eye movement. Here we review the evidence, and conclude that prediction does not in fact play a significant role in maintaining visual stability. Instead, we consider a novel perspective in which the primary function of spatial remapping is to support three key nonperceptual processes: action control, sensorimotor adaptation and spatial memory.